Synthesis of anisotropic colloids with concave and convex structures. Issue 47 (16th November 2021) - Luo, Longfei; Liang, Chengcheng; Zhang, Hong; Zong, Yiwu; Zhao, Kun
Abstract : We synthesized concave particles and checked the mechanism for concavity formation, and then disclosed the relationship between the morphologies of concave seeds and the final fabricated particles. Abstract : Anisotropic colloidal particles with concave and convex structures are useful in both theoretical studies and applications. In this work, we mass-produced polystyrene (PS) colloidal particles with multiple concavities through dispersion polymerization techniques. By increasing the delayed feeding time t d of the cross-linker divinylbenzene (DVB), the morphological evolution of particles can be classified into two stages, during which the formation of different concavities is consistent with either the buckling mechanism or phase separation mechanism. By varying the DVB dosage, we found that the size of the big chamber formed on the particle surfaces decreases as the DVB dosage increases. Then, using these concave particles as seeds, 2–5 μm anisotropic colloids with various shapes, including spherical, ellipsoidal, snowman and multi-protrusion, were synthesized by seeded emulsion polymerization. Moreover, our results show that both the chambers and long narrow ditches on the surface of seeds can be the active sites for monomers to gather and polymerize, but monomers in the big chamber have a priority to polymerize first when big and small concavities both exist on seeds. The results of this study could mean great potential in synthesizing a variety of anisotropic particles with well-controlled concave morphologies.